Analysis of Flow of an Incompressible MHD Third Grade Fluid In An Inclined Rotating Cylindrical Pipes with Isothermal Wall and Joule Heating - G. T., Okedayo; B. I., Obi; M. , Jiya; Y. M., Aiyesimi (International Journal For Research In Mathematics And Statistics, 2021)
In this paper, we considered the analysis of flow of an incompressible MHD third grade fluid in an inclined rotating cylindrical pipes with isothermal wall and Joule heating. The governing equations of the flow field are solved using perturbation method. Results show that the Eckert and the Grashhof parameters reduce the velocity of the fluid flow, while the magnetic field parameter, the Grashhof number, the Eckert number and the third grade parameter increase the temperature of the system. . It is further discovered that the temperature profiles converges to zero at the point where ,which shows that isothermal nature of the outer cylinder.